Which of the following is the correct equation for the Pythagorean Theorem, where a and b are the side lengths and c is the length of the hypotenuse?
A. a^2-b^2=c^2
B. (a+b)^2=c^2
C.(a-b)^2=c^2
D. a^2+b^2=c^2

Respuesta :

Answer:

[tex]\huge \boxed{ \mathrm{D.} \ \ a^2 +b^2 =c^2}}[/tex]

Step-by-step explanation:

The correct equation for the Pythagorean theorem is:

[tex]\Rightarrow \ \ a^2 +b^2 =c^2[/tex]

c is the length of the hypotenuse of the right triangle

a and b are the side lengths of the right triangle

ACCESS MORE